2013
DOI: 10.1186/1746-6148-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Novel lipoprotein density profiling in healthy dogs of various breeds, healthy miniature schnauzers, and miniature schnauzers with hyperlipidemia

Abstract: BackgroundDespite the importance of abnormalities in lipoprotein metabolism in clinical canine medicine, the fact that most previously used methods for lipoprotein profiling are rather laborious and time-consuming has been a major obstacle to the wide clinical application and use of lipoprotein profiling in this species. The aim of the present study was to assess the feasibility of a continuous lipoprotein density profile (CLPDP) generated within a bismuth sodium ethylenediaminetetraacetic acid (NaBiEDTA) dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 22 publications
2
60
0
Order By: Relevance
“…However, Miniature schnauzers have an atypical lipoprotein density profile, independent of whether or not HTG is present (Xenoulis et al, 2013). This suggests that dyslipidemia in the breed is a primary disturbance rather than secondary to renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, Miniature schnauzers have an atypical lipoprotein density profile, independent of whether or not HTG is present (Xenoulis et al, 2013). This suggests that dyslipidemia in the breed is a primary disturbance rather than secondary to renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used in our study previously was shown to identify 11 distinct lipoprotein fractions in dogs based solely on density characteristics . Because the functional characteristics and composition of most lipoprotein density subfractions in dogs currently are unknown, all density subfractions can only be nominally assigned to traditional functional classes such as low‐density lipoproteins (LDL) or high‐density lipoproteins (HDL).…”
Section: Methodsmentioning
confidence: 99%
“…Because the functional characteristics and composition of most lipoprotein density subfractions in dogs currently are unknown, all density subfractions can only be nominally assigned to traditional functional classes such as low‐density lipoproteins (LDL) or high‐density lipoproteins (HDL). Thus, density subfraction data are reported as previously described density ranges identified as R1 to R11 where: R1 ( d < 1.017 g/mL), R2 ( d = 1.019‐1.023 g/mL), R3 ( d = 1.023‐1.029 g/mL), R4 ( d = 1.029‐1.039 g/mL), R5 ( d = 1.039‐1.050 g/mL), R6 ( d = 1.050‐1.063 g/mL), R7 ( d = 1.063‐1.091 g/mL), R8 ( d = 1.091‐1.110 g/mL), R9 ( d = 1.110‐1.133 g/mL), R10 ( d = 1.133‐1.156 g/mL), and R11 ( d = 1.156‐1.179 g/mL) . Based on a previously published classification, and based solely on their density characteristics, these fractions could be classified as: triglyceride‐rich lipoproteins (TRL; chylomicrons and very low‐density lipoproteins [VLDL]; d < 1.017 g/mL), LDL 1 ( d = 1.019‐1.023 g/mL), LDL 2 ( d = 1.023‐1.029 g/mL), LDL 3 ( d = 1.029‐1.039 g/mL), LDL 4 ( d = 1.039‐1.050 g/mL), LDL 5 ( d = 1.050‐1.063 g/mL), HDL 2b ( d = 1.063‐1.091 g/mL), HDL 2a ( d = 1.091‐1.110 g/mL), HDL 3a ( d = 1.110‐1.133 g/mL), HDL 3b ( d = 1.133‐1.156 g/mL), and HDL 3c ( d = 1.156‐1.179 g/mL), respectively .…”
Section: Methodsmentioning
confidence: 99%
“…Manual and automated lipoprotein electrophoresis, density‐gradient ultracentrifugation, various high‐performance liquid chromatography methods, and chemistry analyzers have been used to quantify lipoproteins in dogs. There is currently no established consensus on the gold standard methodology for lipoprotein measurements in dogs . Therefore, it is possible that lipoprotein concentrations measured by a different methodology, such as manual lipoprotein electrophoresis, could yield somewhat different results than those reported in this study.…”
Section: Discussionmentioning
confidence: 72%